Do debate televisivo ao jornal impresso : aforizações na Mídia Nacional - Mareco, Raquel Tiemi Masuda (2013)
The current facility of information access requires that media say and prove what they say, in order to gain the credibility of the reader/listener/viewer and to avoid legal sanctions for releasing libelous, biased or decontextualized information. According to Charaudeau (2006), media communication constitutes a tension between two target: a target that tends to produce an object of knowledge according to civic logic, in other words, a target that aims to inform the public, and a target of commercial, which tends to produce an object of consumption according to a commercial logic: "get the masses to survive the competition" (Charaudeau, 2006, p. 86). Thus, one way to produce an effect of veracity and objectivity, to lessen the responsibility of informing from the enunciator journalist and attract callers, takes place by means of highlight other people's speech. In the media context, the journalist highlights, with or without changes, speeches of others, performing a process that Maingueneau (2008b, 2010) calls aphorisation. The aphorisation is a phenomenon widely used by the media, because to comment about various issues, the media uses the speeches of others to legitimise their say and often need to change other's speeches so that they are understandable by most readers. In this political-media context, this study aims at observing the discursive functioning of aphorisation about the televised debates of the second round presidential elections in 2010 in the newspapers Folha de S. Paulo and O Estado de S. Paulo. The starting point was the following research question: How has been the process of aphorisation construction that circulated in the newspapers? Our theoretical and analytical bias was based mainly on studies of Dominique Maingueneau on detached and detachable statements in dialogue with the concepts of metaphor and paraphrase proposed by Michel Pêcheux. Given these objectives, our research is justified for seeking to contribute with studies on the circulation of political discourse in the media and the influence of the circulation modes in maintaining and/or reframing of the senses. Through the analysis and data presented in the discussion, we noted that most aphorisation was built by suppression and, in many cases, by changing the statements, the scenography built by speech during the debates was not maintained, being changed when stated by the newspapers. These differences in scenography and the image of the politician just benefitting one or another candidate. However, we cannot say that a newspaper has supported a particular candidate because, through the alterations in the construction of aphorisations, the newspapers benefitted one or another candidate.